Changes in physicochemical properties and flavor profiles of roasted tropical almond nuts (Terminalia catappa L.) - Ng, Siew See (2015)
T. catappa is a tropical almond nut which belongs to Combretaceae family and is normally called Indian almond, sea almond, tropical almond, wild almond and etc. In some countries such as Malaysia, Jamaica and Nigeria, this tree is being used for shade and ornament while the edible nuts have been used as snacks or tidbits among the children. Roasting is an important process for nuts and oilseeds because proper roasting is crucial to flavor, color and texture development in the roasted product. Results revealed that moisture and protein content decreased while crude fat content of the nuts increased after roasting process. Besides, decreament of reducing sugar and amino acid content indicated the presence of Maillard reaction in the roasted nuts. This nonenzymatic browning reaction is important in determining consumer‘s acceptability and preferences in nuts. Optimization process revealed that the best roasting conditions for the nuts were of roasting temperature 174.5 ˚C, roasting time 29.9 min and pH 6.08. Color L value decreased from 51.88 to 45.02 whereas color a and b values increased from 3.33 to 3.41 and 8.40 to 9.38, respectively, throughout the roasting process. Meanwhile, browning index increased and fracturability decreased as roasting temperature, roasting time and pH increased. By using gas chromatography-mass spectrometry (GCMS) and gas chromatography olfactometry (GCO) associated with aroma extract dilution analysis (AEDA), flavor compounds that had flavor dilution (FD) factors equal or greater than 16 were selected as the potent odorants in the almond nuts. 12 and 25 potent odorants were identified in the raw and optimized roasted almond nuts, respectively. In raw nuts, the green, sweet and fruity odour impressions were correlated to hexanal, (E)-2-hexenal, hexanol, 2-hexenol, nonanal, ɣ-dodecalactone and ʆ- dodecalactone. On the other hand, dimethylthiazole, octanal, acetylthiazoline, dihydromethylcyclopentapyrazine, (E,E)-2,4-decadienal, decanoic acid, hexadecanone and (E,E)-farnesyl acetate were responsible for the fatty, oily and nutty odour impressions. From the quantification analysis, ɣ-dodecalactone and (E,E)-2,4- decadienal were found to have the highest concentration in raw and roasted nuts respectively. Besides, raw and roasted tropical almond nuts of different roasting levels were analyzed using fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) in order to determine the changes of functional groups and surface morphology of the nuts. FTIR results showed that an increase in temperature did not produce new carbonyl compounds; it however led to higher percentage of transmittance of the carbonyl compounds. On the other hand, SEM results revealed that the nut surface changed from smooth to rough when the nuts were roasted at high temperature. In recent years, there have been limited literatures on the color/flavor changes in roasted T. catappa. Moreover, it is an unexploited nut that had been overlooked and since it has great potential in the food industry, the changes in physicochemical properties as the flavor precursors and flavor profiling of roasted nuts were crucial. Therefore, through this study, we could understand more of the browning changes and also its control in the nuts producing industry.